2014
DOI: 10.1111/aos.12467
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic characteristics of patients with generalized retinal dystrophy in Denmark

Abstract: ABSTRACT.Purpose: To examine socio-economic characteristics of patients with generalized retinal dystrophy in Denmark. Methods: Cross-sectional population-based study with analysis of socio-economic characteristics including income, education, employment status and civil status in 2285 patients from the Danish Retinitis Pigmentosa Registry and 228 500 control subjects matched by age and gender. Demographic and socioeconomic data were retrieved from Statistics Denmark. Differences between cases and controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Bittner and colleagues [12*] state that improving health and quality of life in patients with chronic, disabling conditions, such as RP, involves more than identifying treatments and cures. Therefore, there is a need for a holistic and multidisciplinary approach to understand and provide support for people with RP, that does not only focus on the medical and physiological aspects related to the condition, but also takes into consideration, psychosocial and organizational factors as well [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Bittner and colleagues [12*] state that improving health and quality of life in patients with chronic, disabling conditions, such as RP, involves more than identifying treatments and cures. Therefore, there is a need for a holistic and multidisciplinary approach to understand and provide support for people with RP, that does not only focus on the medical and physiological aspects related to the condition, but also takes into consideration, psychosocial and organizational factors as well [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Visual impairments are also strongly associated with social issues such as employment and education. It has been reported that patients with RP have lower educational levels, lower employment rates, and lower income levels [ 17 ]. A recent report from France supported the idea that RP was closely related to social difficulties which can then lead further mental health problems especially in younger patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of patients with visual impairments, including patients with RP, have reported significant economic and social disadvantage in affected individuals, their families, and society generally. 39,[44][45][46] Patients with visual deficiencies have more frequent medical visits, may need assistance to perform everyday activities, and may have difficulties maintaining employment. Studies have reported that there are significant differences between patients with RP and the general population in terms of education level and income 44 and that patients with RP use more inpatient, outpatient, and emergency department services and prescription drugs.…”
Section: Choroideremia and Associated Vision Loss Have A Significant mentioning
confidence: 99%
“…39,[44][45][46] Patients with visual deficiencies have more frequent medical visits, may need assistance to perform everyday activities, and may have difficulties maintaining employment. Studies have reported that there are significant differences between patients with RP and the general population in terms of education level and income 44 and that patients with RP use more inpatient, outpatient, and emergency department services and prescription drugs. 45 A systematic review of the literature regarding the economic burden of visual impairment and blindness reported high indirect costs primarily related to lost productivity, changes in employment, loss of income, premature mortality, and excess financial burden on society.…”
Section: Choroideremia and Associated Vision Loss Have A Significant mentioning
confidence: 99%